Sexual maturity increases mobility and heterogeneity in individual space use in Atlantic salmon (Salmo salar) parr. Issue 4 (2nd March 2020) - Bouchard, Colin; Lange, Frédéric; Guéraud, François; Rives, Jacques; Tentelier, Cédric
Abstract: We assessed the effects of sexual maturity on space use in Atlantic salmon ( Salmo salar ) parr as facultative early maturation enables us to work on individuals belonging to the same cohort. We monitored the space use of 40 1‐year‐old males in natura throughout a breeding season. First, mature individuals covered longer distances (absolute and upstream) and located within broader home ranges than immature parr. Second, sexual maturity also generated a higher interindividual variability in space use. Finally, mature individuals exhibited a higher probability of association with likely breeding sites on average. However, some mature individuals experienced a lower probability than immature individuals, suggesting that the space use of some mature individuals may not be optimal. Moreover, mature parr exploiting a broader home range or covering longer upstream distances had a higher probability of association with likely breeding sites. Covering longer upstream distances may therefore increase the reproductive success of mature parr, while involving higher energetic costs and a greater risk of predation.